Direct Xa inhibitors in addition to antiplatelet therapy in acute coronary syndrome: meta-analysis of randomized trials. Issue 5 (August 2017) - Villablanca, Pedro A.; Holmes, David; Mohananey, Divyanshu; Briceno, David F.; Núñez Gil, Ivan J.; Kargoli, Faraj; Gupta, Tanush; Kizer, Jorge R.; Bortnick, Anna E.; Wiley, Jose; Menegus, Mark A.; Pyo, Robert; et al.
Abstract : Objective: We carried out a meta-analysis summarizing the efficacy and safety of direct factor Xa inhibitor (DXI) in patients receiving guideline-based antiplatelet therapy (GBAT) after an acute coronary syndrome. Background: Randomized-controlled trials have shown that the addition of a DXI to GBAT after acute coronary syndrome can reduce ischemic events, the trade-off being an increase in major bleeding complications. Methods: PubMed, Central, Embase, The Cochrane Register, Google Scholar databases, and the scientific session abstracts were searched for eligible randomized trials from 1 January 1990 through 31 December 2016. Results: Nine randomized-controlled trials were included in this meta-analysis enrolling a total of 45651 patients. There was a significant reduction in major adverse cardiovascular events with DXIs/GBAT compared with GBAT alone [odds ratio (OR): 0.88; 95% confidence interval (CI): 0.82–0.94, number needed to treat=52]. There were also significant reductions in two individual components of major adverse cardiovascular events: myocardial infarction (OR: 0.89; 95% CI: 0.81–0.98) and stent thrombosis (OR: 0.73; 95% CI: 0.59–0.90), favoring the DXI/GBAT group. There was an increased risk of major bleeding (OR: 2.51; 95% CI: 1.82–3.46) and intracranial hemorrhage (OR: 3.47; 95% CI: 1.76–6.86) compared with GBAT. Conclusion: In acute coronary syndromes, the addition of a DXI to GBAT results in a significant reduction of major adverse cardiovascular events, myocardial infarction, and stent thrombosis, offset by an increased risk of bleeding. Abstract : Supplemental Digital Content is available in the text.